Analyzing situational awareness through public opinion to predict adoption of social distancing amid pandemic COVID‐19. Issue 7 (15th April 2020) - Qazi, Atika; Qazi, Javaria; Naseer, Khulla; Zeeshan, Muhammad; Hardaker, Glenn; Maitama, Jaafar Zubairu; Haruna, Khalid
Abstract: COVID‐19 pandemic has affected over 100 countries in a matter of weeks. People's response toward social distancing in the emerging pandemic is uncertain. In this study, we evaluated the influence of information (formal and informal) sources on situational awareness of the public for adopting health‐protective behaviors such as social distancing. For this purpose, a questionnaire‐based survey was conducted. The hypothesis proposed suggests that adoption of social distancing practices is an outcome of situational awareness which is achieved by the information sources. Results suggest that information sources, formal ( P = .001) and informal ( P = 0.007) were found to be significantly related to perceived understanding. Findings also indicate that social distancing is significantly influenced by situational awareness, P = .000. It can, therefore, be concluded that an increase in situational awareness in times of public health crisis using formal information sources can significantly increase the adoption of protective health behavior and in turn contain the spread of infectious diseases. Highlights: Reducing mortality caused by COVID‐19 can be achieved by awareness. Situation awareness can be increased by formal information sources. Increased situational awareness lead to adoption of health protective behavior.